Lordship and inheritance in early medieval Japan : - Mass, Jeffrey P. (Stanford University Press, 1989)
This book concentrates on the rank-and-file warrior houses that made up the Bakufu's contituency, and examines the social and economic milieu in which these provincial families operated. It is the first full-length study in English of the institutional bases of the medieval Japanese family.